Problems and method of simulation of air conditioning systems of civil aviation aeroplanes - Федоров, М. Ю. (Proceedings of National Aviation University, 2000)
Analyzed ate the existing mathematical methods and models which are connected with computerized simulation of engineering thermal network. Determined are the basical principles of decomposition and technology of development of computer means of simulation of aviation air conditioning system